NiO ELECTRO-DEPOSITION TECHNIQUE OF γ-Al2O3 WASHCOAT ON FeCrAl SUBSTRATE BY USING SULPHAMATE TYPE SOLUTION - Dafit Feriyanto; A. M. Leman; Andi Firdaus Sudarma; Dedik Romahadi; Hadi Pranoto (Universitas Mercu Buana, 2022)
Electro-deposition process to develop surface layer on the substrate material in Catalytic converter (CATCO) become interesting area due to that process was purposed to improve the physical properties of substrate material. Currently, precious metals such as Platinum (Pt), Palladium (Pd), and Rodium (Rd) were used due to excellent oxidation resistant but it limited and easily oxidized. Therefore, Nickel Oxide (NiO) catalyst used as electro-deposition material. NiO electro-deposition technique that called by EL was conducted by using NiO as cathode and FeCrAl as substrate and -Al2O3 as washcoat material. This technique was performed by variation times of 15, 30, 45, 60 and 75 minutes, current density of 8 A/dm2. The results shows that Coating layer of NiO and -Al2O3 has been developed on surface of FeCrAl substrate. The coating layer was increase the surface roughness which showed by surface morphology data that coated FeCrAl substrate has uneven surface and some particles has been embedded on that surface. The composition of raw material was consists of Fe for 74.13wt%, Cr of 20.25 wt% and Al of 5.62 wt%. Meanwhile, for composition of EL samples was 52.56- 63.54wt% for Fe element, Al for 3.56-11.89 wt%, Cr for 14.97-18.56 wt%, O for 2.47-11.78 wt%, C for 8.33-11.85 wt%, Na for 0.11-0.48 wt% and Ni for 0.17- 1.58 wt%. Higher elements of the EL samples potential to improve the thermal stability at high temperature due to CATCO operate at high temperature of 600-8500C and in extreme condition.